Teacher Education - New Perspectives 2021
DOI: 10.5772/intechopen.95998
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Teaching Mathematics with Online Social Networks: The Case of Facebook

Abstract: We present here a study in which a digital-based communication platform is used for collaborative work in the learning and teaching processes. In this case, we focused on Facebook as the online social network to help motivate high-school students to become well prepared for their Bagrut (matriculation) exam in mathematics. To this end, the Center for Educational Technology (CET) established a “virtual review session” on Facebook before the exam in which 614 students and 16 teachers participated. We aimed to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…These platforms would encourage both pupils and teachers the habit of having mathematics intellectual discourses on and off the classroom to better prepare them for their exams. Consistent with Biton and Segal (2021), whose study suggested that Facebook as an online "social network" can be used to help motivate secondary school pupils to become well prepared for their final mathematics examinations.…”
Section: International Journal Of Technology In Education (Ijte)mentioning
confidence: 83%
See 2 more Smart Citations
“…These platforms would encourage both pupils and teachers the habit of having mathematics intellectual discourses on and off the classroom to better prepare them for their exams. Consistent with Biton and Segal (2021), whose study suggested that Facebook as an online "social network" can be used to help motivate secondary school pupils to become well prepared for their final mathematics examinations.…”
Section: International Journal Of Technology In Education (Ijte)mentioning
confidence: 83%
“…There are several studies (e.g. see Arteaga Sánchez, Cortijo, & Javed, 2014;Aydin, 2012;Kaban, 2021a;Mulenga & Marbán, 2020;Susilo, 2014;Biton & Segal, 2021) showing that Facebook is among the social media tools which contribute positively to the educational environment.…”
Section: Marbán Andmulenga 134mentioning
confidence: 99%
See 1 more Smart Citation
“…Seorang guru agar berhasil menerapkan pembelajaran jarak jauh tentu harus mampu membawakan materi pembelajaran dengan efektif dan efisien (Barak et al, 2016). Suatu pembelajaran dikatakan efektif apabila pembelajaran tersebut mampu meningkatkan minat dan motivasi apabila setelah pembelajaran peserta didik menjadi lebih termotivasi untuk belajar lebih giat dan memperoleh hasil belajar yang lebih baik (Biton & Segal, 2021).…”
Section: Latar Belakangunclassified
“…Students must familiarize themselves learning independently with minimal help from the teacher. Students should be more active in digging up information individually rather than in groups which might often be done when lecturing activities are carried out on campus (Biton & Segal, 2021). Online learning activities carried out independently, have eliminated aspects of social interaction that may be established between lecturers-students and students during lectures.…”
mentioning
confidence: 99%